Editorial for the Special Issue "A Themed Issue in Honor of Professor Hartmut Derendorf-Outstanding Contributions in the Fields of Quantitative Clinical Pharmacology" - Françoise Van Bambeke; Sebastian Wicha; Paul M. Tulkens; Markus Zeitlinger (MDPI AG, 2023)
Pharmacokinetics (PK) is the discipline investigating the absorption, distribution, metabolization and elimination of a drug in the body [...]